Comparative Study of Entrepreneurship Intentions Before and During the Covid-19 Pandemic Students of The Faculty of Economics and Business, University of Muhammadiyah Prof. Dr. Hamka - Sunarta Sunarta; Eti Rochaeti (Kusuma Negara Business School, 2022)
Entrepreneurial intentions play a central role in the entrepreneurial process as it is the initial stage of entrepreneurial activity that encourages individuals to start new businesses in a variety of industries. This research aims to find out the entrepreneurship intentions of students of the Faculty of Economics and Business, University of Muhammadiyah Prof. Dr. Hamka before and during the Covid-19 pandemic. The object of the research is a student of the Faculty of Economics and Business UHAMKA. This research uses quantitative methods with comparative analysis, as this type of method is most widely used in entrepreneurial studies and makes it possible to support sample data collection, validation of theories and relationships between collected variables, generalizing the results of the research obtained, and replication of different samples. Two samples were collected through questionnaires taken from students who actively attended lectures before and during the COVID-19 pandemic. The first sample (sample 1) corresponds to the period before COVID-19, with 96 students having been collected between June 2019 and December 2019, while the second sample (sample 2), with 96 students, was collected during the pandemic period between August 2020 and February 2021. Data analysis methods include descriptive statistical tests, normality tests and Wilcoxon sign rank tests. The results showed that the overall indicators of behavioral planning theory, namely attitudes, subjective norms, behavioral control before and during the covid-19 pandemic were different, meaning attitudes, subjective norms and control of student behavior were higher than before the pandemic. Student entrepreneurship intentions are higher during covid-19 than before covid-19.